“Luteal Analgesia”: Progesterone Dissociates Pain Intensity and Unpleasantness by Influencing Emotion Regulation Networks - Vincent, Katy; Stagg, Charlotte J.; Warnaby, Catherine E.; Moore, Jane; Kennedy, Stephen; Tracey, Irene (Frontiers in Endocrinology, 2018)
Background: Pregnancy-induced analgesia is known to occur in association with the very high levels of estradiol and progesterone circulating during pregnancy. In women with natural ovulatory menstrual cycles, more modest rises in these hormones occur on a monthly basis. We therefore hypothesized that the high estradiol high progesterone state indicative of ovulation would be associated with a reduction in the pain experience. Methods: We used fMRI and a noxious thermal stimulus to explore the relationship between sex steroid hormones and the pain experience. Specifically, we assessed the relationship with stimulus-related activity in key regions of networks involved in emotion regulation, and functional connectivity between these regions. Results: We demonstrate that physiologically high progesterone levels are associated with a reduction in the affective component of the pain experience and a dissociation between pain intensity and unpleasantness. This dissociation is related to decreased functional connectivity between the inferior frontal gyrus and amygdala. Moreover, we have shown that in the pre-ovulatory state, the traditionally “male” sex hormone, testosterone, is the strongest hormonal regulator of pain-related activity and connectivity within the emotional regulation network. However, following ovulation the traditionally “female” sex hormones, estradiol and progesterone, appear to dominate. Conclusions: We propose that a phenomenon of “luteal analgesia” exists with potential reproductive advantages.